Hepatic Venous Duplex as an Alternative Non- invasive Diagnostic Tool for Diagnosis of Pulmonary Hypertension - Hoque, Md Harisul; Zaman, SM Mustafa; Ahmed, Khurshid; Banerjee, Sajal Krisna; Kabir, Md Faisal Ibne; Fatema, Nilufar (University Heart Journal, 2020)
Pulmonary hypertension is a hemodynamic disorder defined by abnormally high pulmonary artery pressure that affects the arteries in your lungs and the right side of your heart. In this study, hepatic venous duplex will be done to diagnose and quantify the PH. So that Patients can avoid unnecessary invasive right heart catheterization. This practical demonstration is the key to enrich our experience and knowledge in the field of PH. Objectives of this study was to assess PH status by Hepatic venous Duplex (HVD) as well by right heart catheterization and to compare them. This study was conducted in the Department of Cardiology, BSMMU, Shahbagh, Dhaka extending from July 2018 to December 2019. Total 100 (One hundred) subjects were enrolled in this study. It was an Observational study and includes the subjects between 18 years to 45 years of age. Results of this study shows very close proximity to that of Right heart catheterization. Hemodynamic changes in Hepatic venous duplex study could be used as an alternative diagnostic tool for evaluating moderate to severe pulmonary hypertension. This method could counteract the weakness of the currently used diagnostic methods and improve the accuracy of assessing pulmonary hypertension when combined with other methods. University Heart Journal Vol. 16, No. 2, Jul 2020; 86-91